Evaluasi Kesesuaian Lahan untuk Tanaman Cabai Merah (Capcisum Annuum.,L) di Kecamatan X Koto Kabupaten Tanah Datar - Aprillia, Yolanda; Wilis, Ratna (Al-DYAS, 2024)
The research in X Koto sub-district aim to assess the suitability of land for red chilies and determine the direction of land suitability development. The research method used is descriptive re-search with a quantitative approach, the data used is secondary data and data processing is carried out with fuzzy logc and Bolean logic techniques. The resuls of this study show the land suitability index for red chili plants in X Koto District. Unsuitable land, covering an area of 4986 Ha. The land is suitable enough to be suitable evenly distributed in every village in X Koto District with an area of 5430 Ha. The land is very suitable with an area of 4866 Ha The area of direction for the development of red chili plants in X Koto District which can be developed for red chili plants covering an area of 5128 Ha which is dominant in Nagari Koto Laweh, Aia Angek, Pandai Sikek, Panyalaian. While the area that cannot be developed for red chili plants is 10,157 Ha found in Nagari, Singgalang, and Tambangan.